Wenxiang 3.0: Evolutionary Visualization of α, π, and 3/10 Helices. (May 2022) - Jungck, John R; Cebeci, Metehan
Wenxiang diagrams illustrate protein helices as spirals on a plane and thus have the advantage over helical wheels of being planar graphs. Wenxiang 3.0 extends the original version by adding 3 major features: (1) individual amino acid residues can be colored according to their evolutionary conservation in comparative multiple sequence alignments using CONSURF encoding; (2) α, π, and 3/10 helices can be illustrated by overlaying arcs representative of the pitches of these helices; and, (3) the physico-chemical properties of amino acids residues in the protein sequence can be re-presented by colored geometric shapes.